(untitled) (Research, Society and Development, 2020)
Evaluate the actions for the implementation of the National LGBT Comprehensive Health Plan in primary health care. This study was developed through an integrative review, indexed as databases used in this research: LILACS (Latin American and Caribbean Literature in Health Sciences), BDENF (Nursing Database) and MEDLINE (Medical Literature Analysis ) and Online Recovery System). During a research it was evidenced that the process of vulnerability in health can increase the user’s chance of exposure to illness through individual, collective and contextual conditions, to a greater or lesser degree, susceptibility to physical and psychological illness. It must be necessary that the principles of universality, integrality and equity are the beginnings of SUS materialized in the National Policy for Integral LGBT Care, in fact, promoting the confrontation of exclusionary conditions in health services, as a result of homophobia and heteronormativity.